Sensors : an introductory course - Kalantar-zadeh, Kourosh (Springer, 2013)
Sensors: An Introductory Course provides an essential reference on the fundamentals of sensors. The book is designed to help readers in developing skills and the understanding required in order to implement a wide range of sensors that are commonly used in our daily lives. This book covers the basic concepts in the sensors field, including definitions and terminologies. The physical sensing effects are described, and devices which utilize these effects are presented. The most frequently used organic and inorganic sensors are introduced and the techniques for implementing them are discussed. This book:Provides a comprehensive representation of the most common sensors and can be used as a reference in relevant fields Presents learning materials in a concise and easy to understand mannerIncludes examples of how sensors are incorporated in real life measurementsContains detailed figures and schematics to assist in understanding the sensor performanceSensors: An Introductory Course is ideal for university students at all levels and engineers entering the field with basic background in physics, chemistry and biochemistry as well as electrical, mechanical, and chemical engineers. Researchers and professionals in the area of sensors will also find it to be an invaluable resource.